2021
DOI: 10.1093/deafed/enaa039
|View full text |Cite
|
Sign up to set email alerts
|

Fathers of Young Deaf or Hard-of-Hearing Children: A Systematic Review

Abstract: Much of the literature exploring the role of parents of children who are deaf or hard of hearing (DHH) has focused on mothers; yet, the involvement and perspectives of fathers is valuable and warrants attention. Following the PRISMA guidelines, this systematic literature review examined the peer-reviewed research that has differentially explored the experiences of fathers and mothers of young DHH children. Utilizing three databases (Web of Science, PsychINFO, Scopus) and spanning 50 years (1969–2019), 457 non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Although FCEI for children who are DHH aims to support caregivers in promoting their child's development by addressing the needs of the whole family, the focus of research with this population was centered, to a large extent, on mothers [13]. Less is known about the experiences of fathers, such as the facilitators and barriers to promoting their involvement in EI and their beliefs about their PSE in their role as fathers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although FCEI for children who are DHH aims to support caregivers in promoting their child's development by addressing the needs of the whole family, the focus of research with this population was centered, to a large extent, on mothers [13]. Less is known about the experiences of fathers, such as the facilitators and barriers to promoting their involvement in EI and their beliefs about their PSE in their role as fathers.…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review on the perceptions and experiences of parents of DHH children of 0-6 years of age, which spanned 50 years of research, just 37 studies were identified that explicitly included fathers [13]. The body of research that includes fathers of young DHH children can generally be classified into six themes: (1) fathers' perspectives on parenting;…”
Section: The Importance Of Fathersmentioning
confidence: 99%
“…Gender differences have been found between hearing parents use of spoken language with deaf children (Löfkvist et al., 2022), and there are also differences between hearing and deaf fathers in the amount of visual–tactile interaction strategies and wait‐time they use to gain their child's attention (Loots & Devisé, 2003) and between the number of turns taken by deaf mothers and deaf fathers when interacting with their deaf children (Wille et al., 2019). As recommended by Szarkowski and Dirks (2021), future work should focus on both parents, the mother–father–child triad, or indeed other parent–parent–child dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, lower self-efficacy was reported for parents of children with hearing aids, as compared to parents of children who utilise cochlear implants, which might be related to the amount of support received [ 123 ]. Recently, higher levels of self-efficacy, related to higher levels of involvement in family-centred early intervention and higher levels of received support, were reported, specifically, for fathers of children with HL [ 124 , 125 ]. In accordance, the best practice guideline on family-centred early intervention, for children who are deaf or hard of hearing, emphasises FCEI’s role to promote family well-being (e.g., enjoyment of the child, optimism about the child’s future, emotional availability) and self-efficacy (i.e., the families’ competence and confidence in parenting and promoting the child’s development).…”
Section: Conceptual Modelmentioning
confidence: 99%